Comparative economics and production constraints of leguminous vegetables in vindhyan region - Singh, Neeraj; Roy, Shubhadeep; Bohra, JS; Singh, Anupam (Vegetable Science, 2012)
This study was designed to analyse the comparative economic aspect of leguminous vegetable production such as cowpea and garden pea in underprivileged district of Mirzapur in Vindhyan region which is predominantly a rainfed area. The data were collected from 50 respondents selected randomly and were analyzed by descriptive statistics and gross margin analysis. The findings of the study revealed that per hectare cost of production of garden pea and cowpea were Rs. 29210.87 and Rs. 31461.03 respectively and the corresponding gross incomes were Rs. 94285.59 and Rs. 97261.33 accordingly. The estimated net return of producing garden pea and cowpea were Rs. 65074.72 and Rs. 65800.30 respectively. The results indicated that garden pea growers received the higher B:C ratio (2.23) compared to cowpea (2.09) producers. Some of the major problems identified were lack of quality seeds (60% and 75% in garden pea and cowpea respectively), inadequacy of farm inputs (73.33% in garden pea and 65% in cowpea), labour problem and menace of wild animals. Other problems identified by the farmers were high cost of agro-chemicals and pest management